Pengaruh Tunjangan Sertifikasi Terhadap Kinerja Guru di MTs Nurul Huda Pakandangan Barat Kecamatan Bluto Kabupaten Sumenep Tahun Pelajaran 2021-2022 - Musleh Wahid; Rosidatut Tiniyah (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2023)
Professional teachers are educators who possess specialized abilities and expertise in the field of education, enabling them to fulfill their roles with maximum proficiency. Teachers must strive to understand their students' criteria, identify their talents and interests, and establish good communication and relationships with both students and parents, thereby facilitating their formal and informal development. In this study, the independent variable (X) is certification allowances, while the dependent variable (Y) is teacher performance. The researchers aim to examine the impact of certification allowances on teacher performance at MTs Nurul Huda, West Pakandangan, Bluto District, Sumenep Regency for the 2021/2022 academic year. A quantitative research approach is employed, which necessitates the use of numerical data collection, interpretation, and presentation. The influence level of certification allowances on teacher performance at MTs Nurul Huda Pakandangan Barat Bluto Sumenep falls within the range of 0.80 to 1.000, categorizing it as highly significant. The calculations reveal that certification allowances account for 78.5% of the influence on teacher performance, while the remaining percentage is attributed to other factors.